Nephrolithiasis, bone mineral density, osteoporosis, and fractures: a systematic review and comparative meta-analysis. Issue 11 (November 2016) - Lucato, P.; Trevisan, C.; Stubbs, B.; Zanforlini, B.; Solmi, M.; Luchini, C.; Girotti, G.; Pizzato, S.; Manzato, E.; Sergi, G.; Giannini, S.; Fusaro, M.; et al.
Abstract Summary Our meta-analysis demonstrates that people with nephrolithiasis have decreased bone mineral density, an increased odds of osteoporosis, and potentially an elevated risk of fractures. Introduction People with nephrolithiasis might be at risk of reduced bone mineral density (BMD) and fractures, but the data is equivocal. We conducted a meta-analysis to investigate if patients with nephrolithiasis have worse bone health outcomes (BMD), osteoporosis, and fractures versus healthy controls (HCs). Methods Two investigators searched major databases for articles reporting BMD (expressed as g/cm2 or a T- or Z-score), osteoporosis or fractures in a sample of people with nephrolithiasis, and HCs. Standardized mean differences (SMDs), 95 % confidence intervals (CIs) were calculated for BMD parameters; in addition odds (ORs) for case-control and adjusted hazard ratios (HRs) in longitudinal studies for categorical variables were calculated. Results From 1816 initial hits, 28 studies were included. A meta-analysis of case-control studies including 1595 patients with nephrolithiasis (mean age 41.1 years) versus 3402 HCs (mean age 40.2 years) was conducted. Patients with nephrolithiasis showed significant lower T-scores values for the spine (seven studies; SMD = −0.69; 95 % CI = −0.86 to −0.52;I 2 = 0 %), total hip (seven studies; SMD = −0.82; 95 % CI = −1.11 to −0.52;I 2 = 72 %), and femoral neck (six studies; SMD = −0.67; 95 % CI = −−1.00 to −0.34;I 2 = 69 %). A meta-analysis of the case-controlled studies suggests that people with nephrolithiasis are at increased risk of fractures (OR = 1.15, 95 % CI = 1.12–1.17, p < 0.0001, studies = 4), while the risk of fractures in two longitudinal studies demonstrated trend level significance (HR = 1.31, 95 % CI = 0.95–1.62). People with nephrolithiasis were four times more likely to have osteoporosis than HCs (OR = 4.12, p < 0.0001). Conclusions Nephrolithiasis is associated with lower BMD, an increased risk of osteoporosis, and possibly, fractures. Future screening/preventative interventions targeting bone health might be indicated.